Anticancer and antimicrobial effects of green-synthesized silver nanoparticles using Teucrium polium leaves extract - Aljowaie Reem M.; Aziz Ibrahim M. (Green Processing and Synthesis)
Teucrium polium is a perennial herbaceous plant with a long history of medicinal use in numerous cultures. Silver nanoparticles (AgNPs) using T. polium leaf extract were synthesized and characterized as well as their use in antibacterial and anticancer activities. Ultraviolet–visible spectroscopy, scanning electron microscopy analysis coupled with energy-dispersive X-ray, transmitted electron microscopy (TEM), and Fourier transform infrared spectroscopy analysis validated the effective synthesis. TEM revealed the synthesis of spherical AgNPs ranging in size from 41 to 61 nm. The gas chromatography–mass spectrometry investigation of T. polium leaf extract revealed 10 bioactive components from distinct chemical classes. A test called cytotoxicity showed that AgNPs were toxic to MCF-7 and HepG2 cancer cell lines with the IC50 values = 15 ± 3.18 μg·mL−1 for MCF-7 and 12 ± 2.63 μg·mL−1 for HepG2. It showed high antibacterial activity against Gram-positive and Gram-negative bacteria (minimum inhibitory concentration values ranged from 5.85 ± 2.76 to 31.25 ± 0.00 μg·mL−1). The findings hold promise for developing eco-friendly antibacterial and anticancer agents with enhanced biocompatibility, fostering advancements in both nanotechnology and biomedical sciences, and giving useful insights for future research and development in natural product-based treatments and green nanotechnology.